Lre1 directly inhibits the NDR/lats kinase Cbk1 at the cell division site in a phosphorylation-dependent manner - Mancini Lombardi, Ilde; Meitinger, Franz; Hofmann, Astrid; Pereira, Gislene (Current biology, 2013)
The nuclear Dbf2 related (NDR) family of protein kinases play important roles in cell-cycle regulation, apoptosis, cell morphogenesis, and development in a variety of organisms. In budding yeast, the NDR kinase complex composed of Cbk1 and its regulatory subunit, Mob2, have an established role in the control of cell separation/abscission that follows cytokinesis. Whereas the activators of Cbk1-Mob2 have been more extensively described, the mechanisms that restrict or inhibit Cbk1-Mob2 catalytic activity remain largely unknown. Results: We identified the protein Lre1 as a direct inhibitor of Cbk1-Mob2 catalytic activity. We show that Lre1 accumulates at the cell division site in late anaphase and associates with both Mob2 and Cbk1 in vivo and in vitro. Biochemical and functional analysis established that the ability of Lre1 to associate with Cbk1-Mob2 was reduced by mitotic Cdk1 activity and promoted by Cdc14 phosphatase at the end of mitosis. The inhibition of Cbk1-Mob2 by Lre1 was critical to promote the survival of cells lacking the actomyosin driven pathway of cytokinesis. Conclusions: We established Lre1 as a direct inhibitor of the NDR kinase Cbk1-Mob2, which is regulated in a cell-cycle-dependent manner. We propose that similar inhibitory proteins may also provide fine tuning for the activity of NDR kinases in other organisms.